PHOTOPHYSICAL PROPERTIES OF SOME HETERO-AROMATIC AND CARBONYL COMPOUNDS (2014)
A large number of hetero-aromatic and carbonyl molecules are useful in pharmaceutical and dye industries. Studies of their transition dipole moment (∆μ) and transition polarizability (∆α) are important because they determine their solubility and usefulness. Experimental determination of these parameters and other electronic properties such as oscillator strength (f) using Solvatochromic Shift Equations (SSE) has proved to be unreliable. This is due to the large spread in their reported values and the overlapping of the electronic transition bands for a given molecule. This study was designed to modify the SSE in improving its reliability, and to computationally determine the photophysical properties of some hetero-aromatic and carbonyl compounds with a view to studying the extent of overlap of the electronic transition bands. The ultra-violet spectra of 2,3-diphenylcyclopropenone; 9,10-phenanthrenequinone; Furan-3,4-dicarboxylic acid; 3,4-diphenylthiophene; 3,4-dicarboxylic-2,5-diphenylthiophene and benzo[b]thiophene in the wavenumber range (25,000 - 52,631) cm-1, in solvents of different polarities at concentrations range of 10-6 - 10-5 M were measured at 25oC. These compounds were selected for the modified SSE due to the variation in their structures. The magnitudes of f in solution (fs) and in vapour phase (fv) were calculated using the Onsager-Abe reaction field model equations. The frequencies of electronic transitions in various solvents were used to characterise the observed bands. The SSE was modified by incorporating the molecular ground state polarizability (α), the molar refraction of each compound, Einstein coefficient and stark term. Estimation of the Δµ and Δα of these compounds were determined using the modified SSE. The electronic properties: f, number of transitions, the frontier orbitals energy gap (ΔELUMO-HOMO) and associated parameters such as: Ionization Potential (IP) and global hardness (ƞ) of the optimized structures of the molecules were calculated based on Time-Dependent Density Functional Theory using Becke’s three parameter with Lee-Yang-Parr modification and 6-31G* basis set. The spectra of these compounds gave a range of one to five bands designated as S0-S1, S0-S2, S0-S3, S0-S4 and S0-S5 in order of increasing energy. The magnitudes of fs and fv for the observed bands increased with increasing solvent polarities and were within the range 3.2x10-4 - 1.78 and 3.1x10-4 - 1.33 for hetero-aromatics; 1.4x10-3 - 1.52 and 1.3x10-3 - 1.23 for carbonyls. Similar trends observed for the experimental values of Δµ and Δα indicated that the more a transition is allowed, the greater the probability Δµ being larger than zero. The positive values of Δµ (5.7x10-3 - 1.73D) and Δα (8.0x10-5 - 5.5Å3) for hetero-aromatics; Δµ (3.7x10-2 - 1.23D) and Δα (4.8x10-4 - 0.95Å3) for carbonyls indicated substantial redistribution of the π-electron densities in more polar excited state than the ground state. The ΔELUMO-HOMO were (3.19 - 4.09eV) and (4.36 - 5.43eV) for carbonyls and hetero-aromatics respectively. The IP and ƞ increased as solvent polarity increased, suggesting high stability of these compounds in polar solvents. The modified equation is better in the estimation of transition dipole moment and transition polarizability. The energy gaps and associated parameters suggested strong activity of the molecules and minimal overlapping of the transition bands.